Literature Review: Relationship of Lifestyle with Incidence of Primary Dysmenorrhea in College Students - Maharani, Maharani; Khumairoh, Rizzatul (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Menstruation is periodic and cyclic bleeding from the uterus, accompanied by endometrial desquamation. In specific individuals, menstruation can cause pain called dysmenorrhea, which is characterized by mild, moderate, and severe menstrual pain. Primary dysmenorrhea is not a life-threatening disorder, but it can hurt women's quality of life. Prevalence of menopause in Indonesia An estimated 55% of women of reproductive age experience pain during menstruation. Material and Methods: We searched articles published from 2014-2020 in PubMed, Proquest, and Google Scholar with the keywords